Asabiyyah Concept According to Ibn Khaldun's: An Effort to Overcome Islamic Political Problems in Indonesia - Muhamad Fajar Pramono; Mohammad Latief; Setiawan, Andrie Setiawan Raflie (PERSPEKTIF, 2024)
This article attempts to explore Ibnu Khaldun's views regarding the concept of Asabiyyah which was then linked to the political situation in Indonesia. Issues surrounding the world of politics have been a hot topic of discussion for all Islamic activists and thinkers, which apparently contain various kinds of problems, one of which is the emergence of a group of people who express nationalism but in the end corner other groups and discriminate against them, or what is known as identity politics. This article is a literature review that uses documentary techniques to collect the required data in the form of books, articles and other literature. The result of this article is that the Asabiyah concept essentially refers to the relationship of social solidarity, group spirit and the strength that encourages a group to unite and unite in facing both external and internal challenges. Ibn Khaldun considers that Asabiyyah is something central because a strong group will try to rise and build a power, but will collapse if Asabiyyah begins to fade and weaken.